Service Platform for Integration of Various M2M/IoT System - Phung, Kieu-Ha; Tran, Hieu; Tran-Quang, Vinh (Old Journal, 2020)
The oneM2M is an international partnership project, established to aim at developing the global standard service platform for the Machine-to-Machine (M2M) as well as Internet of Thing (IoT). It promises to allow integration of various communication technology and application protocol in only consolidated open system while in the market, most of M2M/IoT solution are highly vertical and proprietary. oneM2M also can be developed in edge computing environment to process real-time numerous IoT devices’ data. This work provides an overview of oneM2M and several actual implementation results that enable interoperating the disparate layer protocol and multiple technology in a simple scenario.